1982
DOI: 10.1007/bf01391744
|View full text |Cite
|
Sign up to set email alerts
|

Primary gastric lymphoma

Abstract: The records of 50 patients with localized primary gastric lymphoma were reviewed and clinical and prognostic factors characterized. Pathologic material was reclassified according to Rappaport's, Lukes-Collins, and Lennert's Kiel classifications. Factors with the greatest prognostic significance included initial stage as determined by surgery and pathology, absolute tumor size, degree of penetration through the stomach wall, and histologic grade of the lymphoma. After surgical resection for cure, the overall 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…T-------F-material, the Kiel classification system and the International Working Formulation were found to have the better discriminating capabilities (Dragosics et al, 1985;Dworkin et al, 1982). We found a better 1 year survival rate for nodal NHL but a higher 4-year survival rate for patients with primary gastric lymphoma (Figure la).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…T-------F-material, the Kiel classification system and the International Working Formulation were found to have the better discriminating capabilities (Dragosics et al, 1985;Dworkin et al, 1982). We found a better 1 year survival rate for nodal NHL but a higher 4-year survival rate for patients with primary gastric lymphoma (Figure la).…”
Section: Resultsmentioning
confidence: 60%
“…Grading according to the International Working Formulation appeared to be related to survival in our series ( Figures 2 and 4). In other studies only a weak (or no) association was found between prognosis and histological type as given by the Rappaport and/or Lukes-Collins classification system (Dragosics et al, 1985;Dworkin et al, 1982;Haber & Mayer, 1988;Thorling, 1984). When the different classification systems were applied to the same histological -1…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the series of Dragosics et al [16], 2-year disease-free survival is 67% for stage I and 27% for stage II. Different results are reported in the series of Dworkin et al [ 18], indicating 86 and 41 % for stages I and II, respectively. According to the Musshof [39] modification of the Ann Arbor classification, stage II, has almost the same prognosis as stage I,, whereas stage II2 has a much worse prognosis.…”
Section: Prognosismentioning
confidence: 64%